Moderate and high endemicity of schistosomiasis is a predictor of the endemicity of soil-transmitted helminthiasis - Systematic review - Yajima, A. (Trans R Soc Trop Med Hyg, 2011)
The authors conducted a systematic literature review with the following aims: (i) to investigate how frequently soil-transmitted helminthiasis (STH) infections are endemic where schistosomiasis is present; and (ii) to assess the correlation between the risk level of schistosomiasis and that of STH. Among 155 sites on which data were collected and analyzed, schistosomiasis was present in 130 sites, all of which were also co-endemic for STH, whereas 25 sites were endemic only for STH. Out of 83 sites where at least one biannual round of preventive chemotherapy (PC) for schistosomiasis is recommended, 94% were also eligible for at least a yearly round of PC against STH. And among 21 sites where PC for schistosomiasis is recommended once a year, 81% were also eligible for at least a yearly round of PC for STH. This fact provides managers of control programmes with the operationally important indication that use of available information on endemicity of schistosomiasis is a valid tool to predict the presence of STH in the same geographical area as well as to estimate the need of PC for STH. The implementation of this tool is expected to save financial and human resources and help accelerate the scale-up of PC throughout the world.